STUDENTS’ COMPETENCY IN DIFFERENT TYPES OF LISTENING SKILL - I Gusti Agung Vony Purnama (LITERA : Jurnal Bahasa Dan Sastra, 2018)
ABSTRACTThis study aims to find the students’ competency in listening test and also to find out their problemsthrough the listening test result. The students under concern were the second-semester students ofacademic year 2017 taking the English II subject at STIKOM Bali. The data source in this studyis a primary data, which has been got directly from one class of listening comprehension insemester II. This class was chosen since the students of this class have already learned listeningcomprehension for seven meetings. The listening test was consisting of two different types theywere listening comprehension and completing the conversation. The finding shows that the overallperformance of the students in completing the listening conversation was better than theirperformance in listening comprehension. This was caused by the lack of the students’concentration in listening therefore, they could not get the point of that listening, besides that, andthere were also some vocabularies that were uncommon for them.Key words: Listening, Listening Comprehension, Students’ Competency.ABSTRAKTujuan dari peneltian ini adalah untuk mengetahui kompetensi mahasiswa dalam tes listeningsertauntuk mengetahui permasalahan mereka berdasarkan hasil dari tes listening tersebut. Hasiltes listening mahasiswa yang digunakan dalam penelitian ini dari mahasiswa semester duaangkatan 2017 yang mengambil mata kuliah Bahasa Inggris II di STIKOM Bali. Sumber datapenelitian ini adalah data primer, yang diambil langsung dari satu kelas listening comprehensiondi semester II. Kelas Ini dipilih karena mahasiswa di kelas ini sudah memelajari listeningcomprehension selama tujuh pertemuan. Tes listening terdiri dari dua tipe yang berbeda yaitulistening comprehension dan completing the conversation. Temuan pada penelitian inimenunjukkan bahwa secara keseluruhan, hasil tes mahasiswa dalam completing the conversationlebih baik daripada hasil tes listening comprehension. Hal ini disebabkan oleh kurangnyakonsentrasi mahasiswa dalam menyimak sehingga, mereka tidak dapat mengambil inti darilistening tersebut, serta terdapat beberapa kosakata yang jarang mereka dengar sebelumnya.Kata kunci: Listening, Listening Comprehension, Kompetensi Mahasiswa.